2019
DOI: 10.1017/s0950268819001638
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors and outcomes of Candida albicans vs. non-albicans candidaemia in adult patients in Northeast China

Abstract: This study aimed to evaluate the clinical characteristics, risk factors and outcomes of adult patients with candidaemia caused by C. albicans vs. non-albicans Candida spp. (NAC). All adult hospitalised cases of candidaemia (2012–2017) at a tertiary hospital in Shenyang were included in the retrospective study, and a total of 180 episodes were analysed. C. parapsilosis was the most frequently isolated species (38.3%), followed by C. albicans (35.6%), C. glabrata (13.9%), C. tropicalis (10%) and others (2.2%). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 38 publications
5
22
3
Order By: Relevance
“…C. glabrata has already been found to be more frequent in the elderly in previous studies, and there is not a clear explanation for this finding [ 30 , 39 ]. Regarding TPN, the data in the literature are so far inconclusive—there are studies showing the association of TPN with both C. albicans and non-albicans Candida species [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. glabrata has already been found to be more frequent in the elderly in previous studies, and there is not a clear explanation for this finding [ 30 , 39 ]. Regarding TPN, the data in the literature are so far inconclusive—there are studies showing the association of TPN with both C. albicans and non-albicans Candida species [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiological laboratory methods for blood culture, Candida species identification, and antifungal susceptibility testing were performed as previously described [13]. The antifungal susceptibilities of the antifungal agents were evaluated according to clinical breakpoints (CBPs) recommended by the Clinical Laboratory Standards Institute (CLSI) [14] or European Committee on Antimicrobial Susceptibility Testing (EUCAST) [15].…”
Section: Microbiological Analysismentioning
confidence: 99%
“…In previous studies, some differences have been reported between C. albicans and NAC candidemia with regard to the clinical characteristics and prognostic factors. 7–11 However, several limitations are shown as follows: (1) One study identified that the presence of a urethral catheter was an independent risk factor for C. albicans candidemia, 10 and glucocorticosteroids and CVC were independent risk factors for NAC candidemia in another study. 11 However, whether these clinical features are significantly different between these two groups remains unclear.…”
Section: Introductionmentioning
confidence: 99%